An Intercultural Translation and Psychometric Analysis of 18-item Spirituality at Work Questionnaire - Sarallah Shojaei; Sedigheh Sadat Tavafian; Joan Wagner; Ahmad Reza Jamshidi; Ali Mohammadi Valadani (Shahid Beheshti University of Medical Sciences, 2020)
For downloading the full-text of this article please click here. Background and Objective: Spirituality in job is a new topic but with a limited theoretical-scientific development in organizational literature. The importance of this issue and its impact on work efficiency call for a proper instrument for evaluation purposes. Longevity and incomprehensiveness of some of the questionnaires motivated the authors to provide an Intercultural Translation and psychometric analysis of the standard comprehensive instrument of Spirituality at Work. Methods: In this cross-sectional descriptive study, English version of Spirituality at Work scale, adopted from Val Kinjersk's study, was used as the main instrument. An attempt was made to complete English-to-Persian translation as well as to provide cultural conformities using the Wild pattern and recursive translation method and retranslation phases, respectively. Afterwards, face validity was performed based on 10 experts' views and 18 accessible samples and then reliability and validity of the questionnaire were examined and internal correlation was determined in a cross-sectional study on 393 health workers. Construct validity was assessed with a sample size of 268 people through factor analysis. In this study, all the ethical considerations have been observed and no conflict of interest was reported by the authors. Results: To determine construct validity, principal components analysis was performed using Varimax rotation method, in which 70.31% of total variance was explained by two factors. Its face validity was also desirable. In assessing the questionnaire's reliability using internal consistency method, Cronbach's alpha coefficient was found to be 96%, which ranged from 78% to 91% for the subscales. There was a high correlation among subscales of this questionnaire (0/82-0/97). Conclusion: The questionnaire had good consistency and the high correlation between the subscales is indicative of a god cultural consistency in translation of the questionnaire. The questionnaire of Spirituality at Work, which aimed at  assessing the experience of spirituality in job based on individuals' experience of spirituality and workplace morale has proper construct validity and face validity.For downloading the full-text of this article please click here. Please cite this article as: Shojaei S, Tavafian SS, Wagner J, Jamshidi AR, Mohammadi-Valadani A. An Intercultural Translation and Psychometric Analysis of 18-item Spirituality at Work Questionnaire. Pizhūhish dar dīn va salāmat. 2020; 5(4): 114-126. https://doi.org/10.22037/jrrh.v5i4.22349